The Functional Neuroanatomy of Lexical Tone Perception: An Activation Likelihood Estimation Meta-Analysis - Liang, Baishen; Du, Yi (Frontiers in Neuroscience, 2018)
In tonal language such as Chinese, lexical tone serves as a phonemic feature in determining word meaning. Meanwhile, it is close to prosody in terms of suprasegmental pitch variations and larynx-based articulation. The important yet mixed nature of lexical tone has evoked considerable studies, but no consensus has been reached on its functional neuroanatomy. This meta-analysis aimed at uncovering the neural network of lexical tone perception in comparison with that of phoneme and prosody in a unified framework. Independent Activation Likelihood Estimation meta-analyses were conducted for different linguistic elements: lexical tone by native tonal language speakers, lexical tone by non-tonal language speakers, phoneme, word-level prosody, and sentence-level prosody. Results showed that lexical tone and prosody studies demonstrated more extensive activations in the right than the left auditory cortex, whereas the opposite pattern was found for phoneme studies. Only tonal language speakers consistently recruited the left anterior superior temporal gyrus (STG) for processing lexical tone, an area implicated in phoneme processing and word-form recognition. Moreover, an anterior-lateral to posterior-medial gradient of activation as a function of element timescale was revealed in the right STG, in which the activation for lexical tone lied between that for phoneme and that for prosody. Another topological pattern was shown on the left precentral gyrus (preCG), with the activation for lexical tone overlapped with that for prosody but ventral to that for phoneme. These findings provide evidence that the neural network for lexical tone perception is hybrid with those for phoneme and prosody. That is, resembling prosody, lexical tone perception, regardless of language experience, involved right auditory cortex, with activation localized between sites engaged by phonemic and prosodic processing, suggesting a hierarchical organization of representations in the right auditory cortex. For tonal language speakers, lexical tone additionally engaged the left STG lexical mapping network, consistent with the phonemic representation. Similarly, when processing lexical tone, only tonal language speakers engaged the left preCG site implicated in prosody perception, consistent with tonal language speakers having stronger articulatory representations for lexical tone in the laryngeal sensorimotor network. A dynamic dual-stream model for lexical tone perception was proposed and discussed.